2020
DOI: 10.18549/pharmpract.2020.2.2003
|View full text |Cite
|
Sign up to set email alerts
|

Primary health care policy and vision for community pharmacy and pharmacists in Lebanon

Abstract: Within a crippling economic context and a rapidly evolving healthcare system, pharmacists in Lebanon are striving to promote their role in primary care. Community pharmacists, although held in high esteem by the population, are not recognised as primary health care providers by concerned authorities. They are perceived as medication sellers. The role of the pharmacist in primary health care networks, established by the Ministry of Public Health (MOPH) to serve most vulnerable populations, is limited to medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Given the challenges that the profession is facing, pharmacists in Lebanon would gain from emphasizing the public health aspect, particularly in the community and primary care institution. 42 In the same line, a cross-sectional survey of pharmacists practicing in 14 countries in Africa revealed that the competencies within the pharmaceutical care and pharmaceutical public health clusters received higher weighting on relevance. 43 Competencies related to cultural aspects remain of importance in pharmacy education and practice.…”
Section: 41mentioning
confidence: 99%
“…Given the challenges that the profession is facing, pharmacists in Lebanon would gain from emphasizing the public health aspect, particularly in the community and primary care institution. 42 In the same line, a cross-sectional survey of pharmacists practicing in 14 countries in Africa revealed that the competencies within the pharmaceutical care and pharmaceutical public health clusters received higher weighting on relevance. 43 Competencies related to cultural aspects remain of importance in pharmacy education and practice.…”
Section: 41mentioning
confidence: 99%
“…The Order of Pharmacists in Lebanon issued a guidance for community pharmacists to promote their role in educating the public on disease prevention and in referring suspected patients to adequate COVID‐19 centers. Retail pharmacists played important roles as gatekeepers in containing shortages in drugs and medical supplies by controlling over‐dispensation and black market pricing 32 . Finally, many pharmacists in the academic sector were involved in delivering online education and training sessions on COVID‐19 prevention and management measures, as well as in leading and publishing national studies 31 .…”
Section: Lebanonmentioning
confidence: 99%
“…Community pharmacy has been a stronghold for the general public to obtain medication. 74 - 76 Besides, the current policy under the UHC has been a steppingstone for the pharmacist to involve in the primary care system. There is a nexus between pharmacy services and other health services; therefore, an expansion of pharmacist’s roles in partnership with the GPs and other health professionals might be promoted as a new model of comprehensive care, in the prevention, service integration and continuity of care within the system.…”
Section: Way Forwardmentioning
confidence: 99%